2022
DOI: 10.1177/03946320221137435
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin loaded on zinc oxide nanoparticles ameliorates non-alcoholic fatty liver disease associated with insulin resistance in diabetic rats via regulation of PI3K/AKT/FoxO1 pathway

Abstract: Objective Non-alcoholic fatty liver disease (NAFLD) is a worldwide health problem with high prevalence and morbidity associated with obesity, insulin resistance, type 2 diabetes mellitus (T2DM), and dyslipidemia. Nano-formulation of luteolin with Zn oxide in the form of Lut/ZnO NPs may improve the anti-diabetic property of each alone and ameliorate the insulin resistance thus management of NAFLD. This study aimed to measure the efficiency of Lut/ZnO NPs against insulin resistance coupled with NAFLD and T2DM. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 83 publications
(106 reference statements)
0
10
0
Order By: Relevance
“…Luteolin is a natural flavonoid with a variety of pharmacological activities ( 21 ). Luteolin inhibits the expression of TLR4 and JNK mRNA in pancreases of T2DM rats, and it improves IR and alleviates pancreatic inflammatory reactions in T2DM rats ( 22 ). Baicalein is a flavonoid found in traditional Chinese medicine, such as yellow essence and baicalensis, and it has various pharmacological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Luteolin is a natural flavonoid with a variety of pharmacological activities ( 21 ). Luteolin inhibits the expression of TLR4 and JNK mRNA in pancreases of T2DM rats, and it improves IR and alleviates pancreatic inflammatory reactions in T2DM rats ( 22 ). Baicalein is a flavonoid found in traditional Chinese medicine, such as yellow essence and baicalensis, and it has various pharmacological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al investigated the efficacy of Lu-loaded zinc oxide nanoparticles (Lut/ZnO NPs) for treating nonalcoholic fatty liver disease (NAFLD) associated with insulin resistance. 76 Their findings revealed that Lut/ZnO NPs enhanced insulin sensitivity in hepatic cells by activating the PI3K/AKT signaling pathway and inactivating FOXO1, resulting in significant hepatoprotective effects and effectively alleviating the progression of NAFLD. Additionally, Shi et al utilized a magnetic composite Fe 3 O 4 @ZIF-67 as a carrier for delivering Lu, exhibiting a maximum drug loading capacity of 308.07 μg mg −1 and excellent sustained release properties.…”
Section: Nanocarrier Based Systems For Lu Deliverymentioning
confidence: 99%
“…Additionally, reducing luteolin to the nanoscale with zinc oxide showed potential for treating and improving NAFLD by activating the PI3K/AKT signaling pathway, thereby deactivating FoxO1 and potentially improving insulin resistance (Ahmed et al, 2022). Overall, nanoscale delivery of polyphenols holds promise as an approach for liver diseases.…”
Section: Nano-delivery System Of Polyphenols In Liver Diseasesmentioning
confidence: 99%
“…The outcomes indicated effective reversal of hepatic fibrosis attributed to curcumin's capability to interact with proteins involved in fibrosis (PDGFRB, TIMP‐1, TLR‐9, and TGF‐β) (Elzoheiry et al, 2022). Additionally, reducing luteolin to the nanoscale with zinc oxide showed potential for treating and improving NAFLD by activating the PI3K/AKT signaling pathway, thereby deactivating FoxO1 and potentially improving insulin resistance (Ahmed et al, 2022). Overall, nanoscale delivery of polyphenols holds promise as an approach for liver diseases.…”
Section: Nano‐delivery System Of Polyphenols In Liver Diseasesmentioning
confidence: 99%